(untitled) (Eurasian Journal of Ecology, 2016)
We have evaluated the genotoxic potential of oil from Atyrau region in experimental conditions on the lake frog (Rana ridibunda). Furthermore the level of genetic defects was defined for animals of the same species from biotops of Atyrau region which were either under exposure or unaffected by petro pollution. Our results indicated that water-soluble fraction of oil causes a dose-dependent clastogenic effect in the lake frogs under experimental conditions. Also it was established that amphibians from the oil-contaminated areas, have developed genetic damage in somatic cells the level of which greatly exceeds that of the frogs in the experiment.